The mid-tropospheric cyclone: Numerical experimentation (MAUSAM, 1978)
The mid-tropospheric cyclone over the west coast of India has been recognized as playing a major role in producing monsoon rainfall over that region, In this study a real data set is constructed for 1 July 1963 (12 GMT), This initial state represents an early stage in the mid-tropospheric cyclone that was extensively documented by Miller and Keshavamurthy (1968), An x-y-p semi-Lagrangian primitive equation model developed at Florida State University is applied to this data set to make several short-range forecasts, The observed structure of the incipient disturbance indicates that it exists in a favourable dynamic: and thermodynamic environment for development, The forecasts are qualitatively successful, with good rainfall distribution, but the precipitation amounts are too small, In order to develop the kinematic and thermal fields that are quantitatively consistent with the true latent heating rates, a heating function was derived from the observed rainfall totals, The resulting experiments led to more realistic forecasts, as, the mid-tropospheric cyclone intensified as observed, The results of extensive vorticity and energy budget analysis support the hypothesis that the MTC is intensified and maintained by a modified CISK process, in which a cooperative feedback between iarge-scale convergence and convective latent heat release exists without the benefit of a cyclonic Ekman layer.